1966
DOI: 10.1103/physrev.145.218
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of Sn-Zn Eutectic Alloys

Abstract: An experimental study has been made of the superconducting transitions in Sn-Zn eutectic alloys in the temperature range 3.0-3.7°K, employing magnetization measurements on spherical samples. The samples were about 4 mm in diameter, and the laminar spacing varied from 1 to S/x depending on the speed with which the parent ingot had been cooled from the melt. The measurements showed magnetic isotherms approaching those of a type-I superconductor, but with frozen flux of varying degree. The critical-field-versuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that in many eutectic alloys the solute contents and critical fields of the constituent phases are highly sensitive to thermal and mechanical history, and discrepancies in the literature regarding parameters such as critical fields have been attributed to different specimen histories [55]. For example, a critical field of ∼0.1 T was reported by Levy et al for both Sn-Zn and Sn-Cd eutectics [53], whereas other workers reported much lower values for these materials [56]. Similar discrepancies have been reported for Pb-Sb eutectics [53,57].…”
Section: General Properties Of Superconducting Soldersmentioning
confidence: 99%
“…It is worth mentioning that in many eutectic alloys the solute contents and critical fields of the constituent phases are highly sensitive to thermal and mechanical history, and discrepancies in the literature regarding parameters such as critical fields have been attributed to different specimen histories [55]. For example, a critical field of ∼0.1 T was reported by Levy et al for both Sn-Zn and Sn-Cd eutectics [53], whereas other workers reported much lower values for these materials [56]. Similar discrepancies have been reported for Pb-Sb eutectics [53,57].…”
Section: General Properties Of Superconducting Soldersmentioning
confidence: 99%
“…Moreover, Levy et al [19] have observed an influence of the interphase boundary area on the critical current-carrying capacity. The Sn-Zn alloy reported by Lutes et al [20] was a specimen of the second type of eutectic. Despite its lamellar structure, the sample behaved like a homogeneous material due to the appearance of a proximity effect.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two extreme behaviours: properties of eutectic can be a more or less simple sum of the properties of the two phases or it can behave as a completely homogeneous system due to proximity effect. An example of the first case is In-Bi system studied by Currie et al [3], whereas Sn-Zn eutectic reported by Lutes and Clayton [4] behaved like a continuous material with decreasing critical temperature due to the proximity effect. Dobrosavljevic et al [5] observed the effect of proximity on rf surface permeability of Cd-Sn eutectic with superconducting and normal SNSN.…”
Section: Introductionmentioning
confidence: 99%